The Planning and The Development of The Ecotourism and Tourism Village in Indonesia: A policy review - Iwan Nugroho; Purnawan Dwikora Negara; Hefifa Rhesa Yuniar (Publisher of Widyagama University of Malang (UWG Press), 2018)
Developing tourism village or ecotourism requires a carefully integrated planning. The village shows its role and functions as the source of inspiration for environmental and cultural conservation. However, it is not easy to carry out. Developing the tourism village is a great work, multi-sector and requires collaboration. Planning of ecotourism requires the integration of macro, ecosystem and local level. Planning at the macro level gives a legal management basis in the ecosystem and local level. Planning at the ecosystem level devises environmental and cultural vision and coordinates the regional management of a destination. Planning at the local level develops a quality management service, participation, and empowerment of the local people. The development of ecotourism services in the village includes efforts of (i) developing the local empowerment, (ii) developing of infrastructure to meet environmental conservation, (iii) building governance to gain a positive experience and well-being, (iv)integrating the tourism promotion through the product development and market segmentation, and (v) interpreting and educating to offer the education of cultural and environmental conservation. JEL Classification: Q01, Q20, Z38